JUAL BELI ONLINE MELALUI MARKET PLACE TIKTOK SHOP DALAM PERSPEKTIF QOWAID FIQQIYAH - Iffah Febri Anti Fitriyatul Lailiyah; Achmad Fageh (Bussman Journal : Indonesian Journal of Business and Management, 2023)
If everyone has the same awareness, they can optimize the use of available resources. In this case, collaboration will occur to manage unlimited resources in a more structured, efficient and effective manner. One phenomenon that occurs in the economic field is buying and selling transactions through electronic media, known as e-commerce, such as the TikTok Shop feature. The research method used in this study is library research, in which information is collected from various sources of literature through reading and analyzing related books and writings. The approach used in this study is a qualitative descriptive approach. In practice, consent and qabul in buying and selling are not only done verbally, but also through signals and written documents. In this context, consent and acceptance in buying and selling can be done through intermediaries, such as through representatives or using print media such as letters or electronic media such as telephone and email. From the results of the analysis, it can be concluded that there are many marketplaces operating in Indonesia in buying and selling online Apart from that, there are also several fiqhiyah principles which are often used as a guide in the implementation of fiqh products. By using the principles of fiqhiyah, scholars and jurists can develop guidelines for life for Muslims at various times and places